Psychological skills training and a mindfulness-based intervention to enhance functional athletic performance: design of a randomized controlled trial using ambulatory assessment. Issue 1 (December 2016) - Röthlin, Philipp; Birrer, Daniel; Horvath, Stephan; grosse Holtforth, Martin
Abstract Background Struggling to deliver performance in competitions is one of the main reasons why athletes seek the advice of sport psychologists. Psychologists apply a variety of intervention techniques, many of which are not evidence-based. Evidence-based techniques promote quality management and could help athletes, for example, to increase and maintain functional athletic behavior in competitions/games (i.e., being focused on task relevant cues and executing movements and actions in high quality). However, well-designed trials investigating the effectiveness of sport psychological interventions for performance enhancement are scarce. The planed study is founded by the Swiss National Science Foundation and examines the effectiveness of two interventions with elite and sub-elite athletes. A psychological skills training (PST) and a mindfulness-based intervention (MI), administered as group-program, will be compared to a waiting-list control group concerning how they enhance functional athletic behavior - which is a prerequisite for optimal performance. Furthermore, we will investigate underlying mechanisms (mediators) and moderators (e.g., task difficulty, individual characteristics, intervention-expectancy and intervention-integrity). Methods/Design The presented trial uses a randomized controlled design with three groups, comparing PST, MI and a waiting list control condition. Both group interventions will last 5 weeks, consist of four 2 h sessions and will be administered by a trained sport psychologist. Primary outcome is functional athletic behavior assessed using ambulatory assessment in a competition/game. As secondary outcomes competition anxiety, cognitive interference and negative outcome expectations will be assessed. Assessments are held at pre- and post-intervention as well as at 2 months follow up. The study has been approved by the ethical committee of the Swiss Federal Institute of Sport. Discussion Both PST and MI are expected to help improve functional behavior in athletes. By examining potential mechanisms of change and moderators of outcome we will not only be able to answer the question whether the interventions work, but also how, under what conditions, and for whom. This study may also fill a gap in sport psychology research, considering the current lack of randomized controlled trials. In the future, researchers could use the presented study protocol as template to investigate similar topics in sport psychology. Trial registration ISRCTN11147748, date of registration: 11 July 2016.